2009
DOI: 10.1017/s1743921309992833
|View full text |Cite
|
Sign up to set email alerts
|

The formation of an equatorial coronal hole

Abstract: Abstract. The formation of an equatorial coronal hole (CH) from 2006 January 9 to 12 was simultaneously observed by GOES-12/SXI, SOHO/EIT and SOHO/MDI instruments. The varieties of soft X-ray and EUV brightness, coronal temperature, and total magnetic flux in the CH were examined and compared with that of a quiet-sun (QS) region nearby. The following results are obtained. (1) A preexisting dark lane appeared on the location of the followed CH and was reinforced by three enhanced networks. (2) The CH gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They suggested the coronal hole emerges from the unipolar field surrounded by the bipolar field in the active region. Yang et al, [35] studied the formation data of an equatorial coronal hole obtained from GOES-12/SXI, SOHO/EIT and SOHO/MDI. They found that the coronal hole was formed gradually over the period of 81 hours followed by decrease in the magnetic flux, temperature, SXR and EUV brightness.…”
Section: Coronal Holesmentioning
confidence: 99%
“…They suggested the coronal hole emerges from the unipolar field surrounded by the bipolar field in the active region. Yang et al, [35] studied the formation data of an equatorial coronal hole obtained from GOES-12/SXI, SOHO/EIT and SOHO/MDI. They found that the coronal hole was formed gradually over the period of 81 hours followed by decrease in the magnetic flux, temperature, SXR and EUV brightness.…”
Section: Coronal Holesmentioning
confidence: 99%